Bioecologia, competição e hematofagia de Aedes (Stegomyia) aegypti (Linnaeus, 1762) e Aedes (Stegomyia) albopictus (Skuse, 1894) (DIPTERA: CULICIDAE) - Noia, Noiana de Paula (2013)
The Aedes genus is of great epidemiological importance, highlighting the Aedes aegypti Linnaeus, 1762 and Aedes albopictus Skuse, 1894, the main vectors of dengue, yellow fever and other arboviruses. How are spread across the planet, have become a public health risk factors. Aimed to evaluate the effects of temperature on competition and in the life cycle, and the source of blood meal in fecundity and longevity of females of A. aegypti and A. albopictus. The collections of eggs were performed using traps ovitraps type. The experiments were performed at the Laboratory of Entomology, University of Paraíba State - UEPB in Campina Grande, PB. Competition between A. aegypti and A. albopictus was examined at temperatures of 20, 24, 28, 32 and 36 ° C in the proportion of 10:0, 7:3, 5:5, 3:7 and 10:0 (A. aegypti : A. albopictus). The cycle life was examined at the same temperatures. Feeding two treatments with each meal in quail and the other in swiss mice were used. For all experiments we used 12h light and 70% humidity. In interspecific relationship, there was overlap of A. aegypti on A. albopictus from the first generation (F1), independent of temperature and the proportion of species. The long life cycle did not differ significantly among species independent of temperature, but decreased with increasing temperature. The base temperature (Tb) and thermal constant (K) and hence the number of generations was greater for A. albopictus than for A. aegypti. The repast in mice resulted in greater number of eggs and female longevity for both A. aegypti as for A. albopictus. The substrate used for biting that was more appropriate for the two species, the mouse was, since we obtained the highest female fertility and longevity. The temperature and the substrate used for blood feeding interfere with competition, development, longevity and fecundity of the species studied. The number of generations of insects in the laboratory is higher for A. albopictus than for A. aegypti.